Minimum Inhibitory Concentration Distribution of Fluconazole Against Cryptococcus Species and the Fluconazole Exposure Prediction Model. (17th August 2019) - Chesdachai, Supavit; Rajasingham, Radha; Nicol, Melanie R; Meya, David B; Bongomin, Felix; Abassi, Mahsa; Skipper, Caleb; Kwizera, Richard; Rhein, Joshua; Boulware, David R
Abstract: Background: Fluconazole is lifesaving for treatment and prevention of cryptococcosis; however, optimal dosing is unknown. Initial fluconazole doses of 100 mg to 2000 mg/day have been used. Prevalence of fluconazole nonsusceptible Cryptococcus is increasing over time, risking the efficacy of long-established standard dosing. Based on current minimum inhibitory concentration (MIC) distribution, we modeled fluconazole concentrations and area under the curve (AUC) relative to MIC to propose a rational fluconazole dosing strategy. Method: We conducted a systematic review using the MEDLINE database for reports of fluconazole MIC distribution against clinical Cryptococcus isolates. Then, we utilized fluconazole concentrations from 92 Ugandans who received fluconazole 800mg/day coupled with fluconazole's known pharmacokinetics to predict plasma fluconazole concentrations for doses ranging from 100 mg to 2000 mg via linear regression. The fluconazole AUC above MIC ratio were calculated using Monte Carlo simulation and using the MIC distribution elucidated during the systemic review. Results: We summarized 21 studies with 11 049 clinical Cryptococcus isolates. Minimum inihibitory concentrations were normally distributed with a geometric mean of 3.4 µg/mL, median (MIC50 ) of 4 µg/mL, and 90 th percentile (MIC90 ) of 16 µg/mL. The median MIC50 trended upwards from 4 µg/mL in 2000–2012 to 8 µg/mL in 2014–2018. Predicted subtherapeutic fluconazole concentrations (below MIC) would occur in 40% with 100 mg, 21% with 200 mg, and 9% with 400 mg. The AUC:MIC ratio >100 would occur in 53% for 400 mg, 74% for 800 mg, 83% for 1200 mg, and 88% for 1600 mg. Conclusions: Currently recommended fluconazole doses may be inadequate for cryptococcosis. Further clinical studies are needed for rational fluconazole dose selection. Abstract : The systematic review demonstrates the uptrend in the minimum inhibitory concentration of fluconazole against Cryptococcus species. Based on the fluconazole pharmacokinetic data, the historically recommended fluconazole dose for cryptococcal meningitis treatment may not be adequate enough to reach an optimal therapeutic goal.